A Proposed Framework for Fingerprint-based Voting System in Bangladesh - Nahida Nigar; Mohan Lal Nath; MD. Toufiqul Islam (Politeknik Negeri Padang, 2020)
The objective of this project is to improve the existing voting system that will be accurate, transparent, and faster and will ensure a single vote for a single person. Our proposed system has covered all of these issues successfully. This product is affordable by many organizations where preferential elections conducted. The product is a prototype and can be implemented for vast use. Voting is an onerous task for the election commission to conduct free and fair polls in our country, the largest democracy in the world. A lot of money has been spent on this to make sure that the elections are rampage free. But, now- a -days it has become very usual for some forces to indulge in rigging which may eventually lead to a result contrary to the actual verdict given by the people. In order to provide inexpensive solutions to the above, this project is implemented with the biometric system i.e. fingerprint scanning. This is used to ensure the security to avoid fake, repeated voting, etc. It also enhances the accuracy and speed of the process. The system uses a thumb impression for voter identification as we know that the thumb impression of every human being has a unique pattern. Thus it would have an edge over the present-day voting systems. The purpose of such a system is to ensure that the voting rights are accessed only by a legitimate user and no one else. In this, creation of a database consisting of the thumb impressions of all the eligible voters in a constituency is done as a pre-poll procedure. During elections, the thumb impression of a voter is entered as input to the system. This is then compared with the available records in the database. If the particular pattern matches with anyone in the available record, access to cast a vote is granted. But in case the pattern doesn’t match with the records of the database or in case of repetition, access to cast a vote is denied or the vote gets rejected. The result is instantaneous and counting is done. The overall cost for conducting elections gets reduced and so does the maintenance cost of the systems.